Pengaruh Penerapan Keselamatan dan Kesehatan Kerja (K3) terhadap Kinerja Pegawai di PT. Taiyo Sinar Raya Teknik Bekasi - Andriyani Andriyani; Adriza Adriza; Hadi Mulyo Wibowo (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of the implementation of Occupational Safety and Health on employee performance at PT. Taiyo Sinar Raya Teknik Bekasi. Occupational Safety and Health is one of the important factors in creating a safe, comfortable work environment that supports employee productivity. The method used in this study is a quantitative method with a descriptive and verification approach. Data were obtained by distributing questionnaires to respondents who were employees of PT. Taiyo Sinar Raya Teknik. The results of the study showed that the implementation of K3 was in the good category with an average score of 4.02. Employee performance was also in the good category with an average score of 3.97. Based on the results of statistical analysis, it is known that the implementation of K3 has a positive and significant effect on employee performance with a contribution of 64.1%, while the remaining 35.9% is influenced by other variables outside this study. Thus, it can be concluded that the better the implementation of K3 in the company, the higher the employee performance. Therefore, the company needs to continue to improve the implementation of the K3 program and pay attention to other factors that influence performance so that productivity and work safety can be improved sustainably.